Bryce 4 f/x and design - Mortier, R. Shamms (Coriolis Group Books, 1999)
32 full-color pages of ethereal, sci-fi, and Dali-esque 3D backgrounds and imagery (also on the accompanying CD) that caters to Bryce users who want to create unusual artwork. The only book to cover handshaking with MetaCreations' Poser, Ray Dream, and Painter. Unlike competing titles ,Bryce 4 f/x and design will cover film and video techniques and will teach the complexity of the software in an approachable, easy-to-follow manner. Delves into the secrets of the Deep Texture Editor and fine-tunes all of the new materials made possible in the Materials Lab.